PERAN PUPUK HAYATI UNTUK PENINGKATKAN HASIL CAISIM, RESIDU KETERSEDIAAN N DAN P SERTA SERAPANNYA PADA TANAMAN - Reginawanti Hindersah; Adita Rizky Syntianis; Ade Setiawan; Rina Devnita (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2021)
Consortium biofertilizer containing Nitrogen (N) Fixing Bacteria and Phosphate (P) Solubilizing Bacteria may substitute inorganic fertilizer in vegetable production. A greenhouse experiment was conducted to evaluate the effect of some combinations and doses of consortium biofertilizer and NPK compound fertilizer on available N and P in the soil, fresh weight of caysim (Brassica chinensis L. var. parachinensis.), and their uptake by caisim shoots after grown in low fertility soil. The experimental design was a randomized block design consisting of seven combinations and doses of consortium biofertilizer and compound fertilizer; and three control treatments. All treatments were repeated three times. The results showed that the combination of the which combination treatment of inorganic fertilizer and biofertilizer had a significant effect on the fresh weight of caysim shoots, available P and N and P uptake after harvesting compared to the biofertilizer treatment alone or without fertilization. Several treatments of combined doses of biofertilizers and NPK compound fertilizer produced the same yield as NPK compound fertilizer alone. The application of 300 kg/ha of compound fertilizer combined with 3,75 L/ha of biofertilizer enabled to increase the yield up to 16% compared to NPK fertilizer alone. This experiment explained that inoculation of biofertilizers can reduce the dose of NPK fertilizer to maintain yield, available P residue in soil and P uptake